Battery cell and method for producing the same, battery device, electric device

CN123017878APending Publication Date: 2026-10-30CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510570263.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-30
Publication Date
2026-10-30

Smart Images

  • Figure CN123017878A_ABST
    Figure CN123017878A_ABST
Patent Text Reader

Abstract

A battery monomer, a preparation method thereof, a battery device, and a power utilization device. The battery monomer comprises a negative electrode sheet, the negative electrode sheet comprises a negative electrode current collector and a negative electrode film layer arranged on at least one side surface of the negative electrode current collector, the negative electrode film layer comprises a negative electrode active material, and the negative electrode active material comprises graphite; an interlayer spacing D of the graphite satisfies 0.33589 nm<=D<=0.3364 nm; and a gram capacity C of the graphite satisfies 330 mAh / g<=C<=360 mAh / g. The technical scheme of the application is beneficial to improving the cycle performance and storage performance of the battery monomer while taking into account the capacity performance of the battery monomer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of battery technology, and more specifically, to a battery cell and its preparation method, a battery device, and an electrical device. Background Technology

[0002] In recent years, with the increasingly wide range of applications, batteries have been widely used in energy storage power systems such as hydropower, thermal power, wind power and solar power plants, as well as in many fields such as power tools, electric bicycles, electric motorcycles, electric cars, military equipment, and aerospace.

[0003] The development of battery technology requires consideration of various design factors, such as energy density, cycle life, storage performance, charge / discharge rate, and reliability. While battery cells have made significant strides, higher demands have been placed on their performance in all aspects.

[0004] Therefore, how to improve the performance of individual battery cells is a technical problem that urgently needs to be solved. Summary of the Invention

[0005] This application is made in view of the above-mentioned problems, and its purpose is to provide a battery cell and its preparation method, battery device and power device, so as to improve the cycle performance and storage performance of the battery cell while taking into account the capacity performance.

[0006] In a first aspect, a battery cell is provided, comprising: a negative electrode sheet, the negative electrode sheet comprising a negative current collector and a negative electrode film layer disposed on at least one surface of the negative current collector, the negative electrode film layer comprising a negative electrode active material, the negative electrode active material comprising graphite; the interlayer spacing D of the graphite satisfies: 0.33589nm≤D≤0.3364nm; the specific capacity C of the graphite satisfies: 330mAh / g≤C≤360mAh / g.

[0007] In this embodiment, under the condition of constant specific capacity, selecting graphite with a higher specific capacity and increasing the interlayer spacing of the graphite helps to reduce volume expansion caused by lithium-ion intercalation / deintercalation during charging and discharging, thereby improving the cycle stability and capacity performance of the battery cell. On the other hand, this interlayer spacing can also lower the diffusion barrier of lithium ions between graphite layers and reduce lithium-ion retention by mitigating strain during lithium intercalation, thus improving the storage performance of the battery cell. Simultaneously, while the graphite has a large interlayer spacing, the tortuous lattice fringes of the graphite prevent breakage of the lattice growth fringes and avoid graphite layer peeling. Therefore, the number of lithium storage sites between graphite layers is not reduced, which allows the specific capacity of the graphite to remain constant, benefiting the capacity performance of the battery cell. Therefore, using graphite with a fixed specific capacity in the negative electrode sheet can increase the interlayer spacing of the graphite, which is beneficial to improving the cycle performance and storage performance of the battery cell while also maintaining its capacity performance.

[0008] In some embodiments, the degree of graphitization g of the graphite satisfies: 87.9% ≤ g ≤ 94.2%.

[0009] In the embodiments of this application, the graphite has a large interlayer spacing, so that its graphitization degree meets the above-mentioned range.

[0010] In some embodiments, the tap density T of the graphite satisfies: 0.9 g / cm³ 3 ≤T≤1.3g / cm 3 Optionally, the tap density T of the graphite satisfies: 1.0 g / cm³. 3 ≤T≤1.25g / cm 3 .

[0011] In this embodiment, the tap density of graphite meets the above-mentioned range, which helps to improve the energy density of the battery cell while also taking into account its capacity performance. By further adjusting the tap density of graphite, the performance of the battery cell can be further improved.

[0012] In some embodiments, the Dv50 of the graphite satisfies: 10.0 μm ≤ Dv50 ≤ 18.0 μm; optionally, the Dv50 of the graphite satisfies: 10.5 μm ≤ Dv50 ≤ 16.6 μm.

[0013] In the embodiments of this application, the Dv50 of graphite meets the above-mentioned range, which can not only reduce the impact on the cycle storage performance of battery cells due to excessively large specific surface area caused by too small Dv50, but also reduce the impact on rate performance caused by excessively large Dv50, which results in a longer migration path of lithium ions inside graphite particles.

[0014] In some embodiments, the unilateral density ρ of the negative electrode film layer satisfies: 100 mg / 1540.25 mm². 2 ≤ρ≤170mg / 1540.25mm 2 .

[0015] In this embodiment, setting the coating weight of the negative electrode film within the above-mentioned range is beneficial to balancing the energy density and service life of the battery cell.

[0016] In some embodiments, the graphite includes synthetic graphite.

[0017] In the embodiments of this application, a suitable type of graphite can be selected according to the requirements of the battery cell.

[0018] In a second aspect, a method for preparing a battery cell is provided, comprising: adding an oxidant solution to a graphite raw material for pre-oxidation treatment to obtain a pre-oxidized graphite solution; wherein the oxidant solution includes an oxidant; adding a reducing agent solution to the pre-oxidized graphite solution and generating gas in a redox reaction to obtain a graphite solution; wherein the reducing agent solution includes a reducing agent; stirring, filtering, washing and drying the graphite solution to obtain graphite; and using the graphite to prepare a negative electrode sheet to obtain the battery cell.

[0019] In this embodiment, the above-described preparation method, through pre-oxidation treatment, can micro-expand the edge layers of the graphite raw material. On one hand, this removes some defect sites on the surface of the graphite raw material, thereby improving the storage performance of the battery cell. On the other hand, it also facilitates the easier intercalation of the reducing agent into the interlayer of the graphite. Subsequently, the gas generated during the redox reaction further increases the interlayer spacing of the graphite. This reduces the volume expansion of graphite during cycling, thereby reducing the loss of excessive active lithium due to the rupture and repair of the SEI film caused by the expansion and contraction of graphite particles during cycling, which affects its cycle performance. In addition, while the graphite has a large interlayer spacing, the gas generation causes the graphite lattice fringes to bend, preventing the graphite lattice growth fringes from breaking or the graphite sheets from peeling off. This ensures that the lithium storage sites between the graphite layers are not reduced, and the specific capacity remains unchanged, thus benefiting the capacity performance of the battery cell. Therefore, the above-described preparation method can improve the cycle performance and storage performance of the battery cell while also considering capacity performance.

[0020] In some embodiments, the oxidant includes at least one selected from nitric acid, sulfuric acid, ammonium persulfate, potassium permanganate, potassium dichromate, hydrogen peroxide, and ozone.

[0021] In the embodiments of this application, these oxidants all have strong oxidizing properties and can selectively oxidize and etch the active sites at the edges of graphite, thereby introducing oxygen-containing functional groups at the edges or between layers of graphite.

[0022] In some embodiments, the reducing agent comprises an organic acid, which includes at least one of a carboxylic acid group and a sulfonic acid group.

[0023] In the embodiments of this application, these weakly acidic organic acids are used, which can undergo redox reactions with the aforementioned oxygen-containing functional groups, transforming the aforementioned edge active sites into more stable SPs. 2 The conjugated structure effectively reduces the number of active sites on the graphite surface. This reduces irreversible lithium consumption during SEI film formation, thus improving the cycle performance of individual battery cells.

[0024] In some embodiments, the reducing agent includes at least one selected from formic acid, acetic acid, propionic acid, oxalic acid, citric acid, benzoic acid, p-toluenesulfonic acid, and benzenesulfonic acid.

[0025] In the embodiments of this application, the use of these reducing agents with strong reducing properties is beneficial to further expand the interlayer spacing and also to enhance its stability.

[0026] In some embodiments, based on the total mass of the graphite solution, the mass content A of the reducing agent satisfies: 16% ≤ A ≤ 50.4%; alternatively, the mass content A of the reducing agent satisfies: 16% ≤ A ≤ 20%.

[0027] In the embodiments of this application, setting the mass content of the reducing agent within the above-mentioned range is beneficial to the layer expansion effect and interlayer structure of graphite, thereby improving the performance of the battery cell.

[0028] In some embodiments, based on the total mass of the graphite solution, the mass content B of the oxidant satisfies: 20% ≤ B ≤ 75%; alternatively, the mass content B of the oxidant satisfies: 55% ≤ B ≤ 68%.

[0029] In the embodiments of this application, the mass content of the oxidant meets the above range, which can improve the layering effect on graphite and also improve the cycle performance.

[0030] In some embodiments, the temperature E of the pre-oxidation treatment satisfies: 20℃≤E≤60℃.

[0031] In the embodiments of this application, the temperature of the pre-oxidation treatment meets the above-mentioned range, which can eliminate surface active sites and expand the interlayer spacing, and can also reduce the breakage of graphite particles due to excessive oxidation, thereby exposing more active sites.

[0032] In some embodiments, the concentration w of the oxidant solution satisfies: 50% ≤ w ≤ 90%.

[0033] In the embodiments of this application, the effect of graphite layer expansion can be further improved by controlling the concentration of the oxidant solution.

[0034] In some embodiments, the molecular weight of the oxidant is greater than the molecular weight of the reducing agent.

[0035] In the embodiments of this application, the selection of an oxidant with a larger molecular weight can effectively expand the interlayer space of graphite, which makes it easier for a smaller reducing agent to penetrate into the expanded interlayer space of graphite, thereby helping to expand the interlayer space of graphite.

[0036] In some embodiments, the graphite raw material includes at least one of artificial graphite, modified natural graphite, mesophase carbon microspheres, petroleum coke, and needle coke.

[0037] In the embodiments of this application, a suitable graphite raw material can be selected according to the actual usage requirements of the negative electrode sheet.

[0038] In some embodiments, the pre-oxidation treatment time F satisfies: 10min≤F≤24h, and the stirring speed V satisfies: 100rpm≤V≤800rpm.

[0039] In the embodiments of this application, the time and stirring speed of the pre-oxidation treatment described above can further improve the layer expansion effect, thereby improving the performance of the battery cell.

[0040] Thirdly, a battery device is provided, comprising a battery cell according to the first aspect and any possible implementation thereof, and / or a battery cell obtained by a preparation method according to the second aspect and any possible implementation thereof.

[0041] Fourthly, an electrical device is provided, including the battery device described in the third aspect. Attached Figure Description

[0042] To more clearly illustrate the technical solutions of the embodiments of this application, the drawings used in the embodiments of this application will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on the drawings without creative effort.

[0043] Figure 1 This is a schematic diagram of the negative electrode sheet according to one embodiment of this application;

[0044] Figure 2 This is a schematic diagram of a battery cell according to one embodiment of this application;

[0045] Figure 3 This is a schematic diagram of the structure of a battery cell according to another embodiment of this application;

[0046] Figure 4 This is a flowchart illustrating the preparation process of a battery cell according to one embodiment of this application.

[0047] Figure 5 This is a schematic diagram of a battery device according to one embodiment of this application;

[0048] Figure 6 This is a schematic diagram of the structure of a battery device according to an embodiment of this application;

[0049] Figure 7 This is a schematic diagram of the structure of an electrical device according to an embodiment of this application;

[0050] Figure 8 This is a TEM image of the graphite in Embodiment 3 of this application;

[0051] Figure 9 The XRD patterns are of graphite from Examples 2-3 and Comparative Example 1 of this application;

[0052] Figure 10 The Raman spectra of graphite in Examples 2-3 and Comparative Example 1 of this application are shown.

[0053] Figure label:

[0054] 1-Vehicle; 11-Housing; 12-Electrode assembly; 121-Negative electrode sheet; 1211-Negative current collector; 1212-Negative electrode film; 13-Cover plate; 100-Battery cell; 400-Battery assembly; 401-Upper casing; 402-Lower casing; 500-Motor; 600-Controller.

[0055] The accompanying drawings are not drawn to scale. Detailed Implementation

[0056] The following detailed description of the battery cell, its preparation method, battery device, and power-consuming device of this application, with appropriate reference to the accompanying drawings, may omit unnecessary details. For example, detailed descriptions of well-known matters and repetitive descriptions of practically identical structures may be omitted. This is to avoid unnecessarily lengthy descriptions and to facilitate understanding by those skilled in the art. Furthermore, the accompanying drawings and the following description are provided for the purpose of enabling those skilled in the art to fully understand this application and are not intended to limit the subject matter of the claims.

[0057] The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of a particular range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a specific parameter, it is expected that ranges of 60-110 and 80-120 are also included. Furthermore, if minimum range values ​​of 1 and 2 are listed, and if maximum range values ​​of 3, 4, and 5 are listed, then the following ranges are all expected: 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5. In this application, unless otherwise stated, the numerical range "ab" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0-5" indicates that all real numbers between "0-5" have been listed in this article; "0-5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is stated as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0058] Unless otherwise defined, all technical and scientific terms used in this application have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains; the terminology used in the description of this application is for the purpose of describing particular embodiments only and is not intended to limit the application; the terms "comprising" and "having," and any variations thereof, in the description, claims, and accompanying drawings of this application are intended to cover non-exclusive inclusion. The terms "first," "second," etc., in the description, claims, or accompanying drawings of this application are used to distinguish different objects, not to describe a specific order or hierarchy.

[0059] Unless otherwise specified, all embodiments and optional embodiments of this application can be combined to form new technical solutions.

[0060] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions.

[0061] Unless otherwise specified, all steps in this application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, the mention that the method may also include step (c) indicates that step (c) may be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.

[0062] The development of battery technology must consider multiple design factors simultaneously, such as energy density, cycle life, discharge capacity, charge / discharge rate, and reliability. To develop battery cells that combine high energy density and long cycle life, improving the specific capacity of the anode material is crucial. Among these materials, graphite is widely used due to its good conductivity, stable structure, and low cost.

[0063] To address these issues, relevant technologies typically employ graphite with higher specific capacity and perform layer-expansion treatments to increase the interlayer spacing. Higher specific capacity improves the energy density of individual battery cells, while increasing the interlayer spacing enhances cycle performance. However, current methods often utilize high-temperature heat treatment (such as calcination and carbonization) to modify the graphite structure. This process is not only complex but also ineffective in increasing interlayer spacing. It can lead to breakage of graphite lattice growth striations, delamination of graphite layers, and reduced graphitization, ultimately decreasing the specific capacity of the battery cells and consequently reducing their capacity performance.

[0064] In view of the above, embodiments of this application provide a battery cell, including: a negative electrode sheet, the negative electrode sheet including a negative current collector and a negative electrode film layer disposed on at least one side surface of the negative current collector, the negative electrode film layer including a negative electrode active material, the negative electrode active material including graphite; the interlayer spacing D of the graphite satisfies: 0.33589nm≤D≤0.3364nm; the specific capacity C of the graphite satisfies: 330mAh / g≤C≤360mAh / g.

[0065] In the above technical solution, under the condition of constant specific capacity, selecting graphite with a higher specific capacity and setting the interlayer spacing of the graphite within the above range can increase the interlayer spacing of the graphite material. This can alleviate the volume expansion of graphite caused by lithium insertion / extraction during charging and discharging, thereby improving the cycle performance of the battery cell. On the other hand, this interlayer spacing can reduce the diffusion barrier of lithium ions between graphite layers and reduce the phenomenon of lithium ion retention by alleviating lithium insertion strain, thereby improving the storage performance of the battery cell. At the same time, after the graphite is expanded, the lattice stripes of the graphite are curved, which will not cause the lattice growth stripes of the graphite to break or the graphite sheets to peel off. Therefore, the lithium storage sites between graphite layers will not decrease, which can keep the specific capacity of the graphite constant. In other words, the graphite has a large interlayer spacing without affecting the capacity performance of the battery cell. Therefore, the graphite in the embodiments of this application can increase the interlayer spacing of the graphite when the specific capacity is fixed, which is beneficial to improving the cycle performance and storage performance of the battery cell while taking into account its capacity performance.

[0066] The following description, with reference to the accompanying drawings, illustrates the battery cell, its preparation method, battery device, and power-consuming device of this application.

[0067] [Battery cell]

[0068] This application provides a single battery cell. Typically, a single battery cell includes a positive electrode, a negative electrode, an electrolyte, and a separator. During the charging and discharging process of the battery cell, active ions repeatedly insert and extract between the positive and negative electrodes. The electrolyte, acting as a conductor for the active ions, lies between the positive and negative electrodes. The separator, positioned between the positive and negative electrodes, primarily prevents short circuits between the positive and negative electrodes while allowing the passage of active ions. In some embodiments, the above-mentioned battery cell is also referred to as a secondary battery, and the battery cell can be the smallest possible battery unit.

[0069] The technical solution of this application can be applied to various battery cells, such as lithium-ion batteries, sodium-ion batteries, potassium-ion batteries, etc., and this application does not limit it. It should be noted that, for the sake of convenience, this application uses lithium-ion batteries as an example for illustration.

[0070] During the charging process of a lithium-ion battery, lithium ions are released from the positive electrode active material, move and embed into the negative electrode material; while during the discharging process, lithium ions are released from the negative electrode material, move and embed into the positive electrode active material.

[0071] It should be understood that the “intercalation” process described in this application refers to the process in which lithium ions are intercalated in the positive electrode active material and the negative electrode material due to an electrochemical reaction, and the “deintercalation” and “deintercalation” processes described in this application refer to the process in which lithium ions are deintercalated in the positive electrode active material and the negative electrode material due to an electrochemical reaction.

[0072] Next, the negative electrode, positive electrode, electrolyte, and separator of this application will be described with appropriate reference to the accompanying drawings.

[0073] [Negative electrode plate]

[0074] The negative electrode sheet may include a negative current collector and a negative electrode film layer disposed on at least one side surface of the negative current collector, the negative electrode film layer including a negative electrode active material.

[0075] Figure 1 This is a schematic diagram of the structure of a negative electrode sheet according to an embodiment of this application. Figure 1 As shown, the negative electrode 121 includes a negative current collector 1211 and a negative electrode film layer 1212 disposed on at least one side surface of the negative current collector 1211.

[0076] The negative electrode current collector 1211 has two opposing surfaces along its thickness direction. The negative electrode film layer 1212 can be disposed on one surface of the negative electrode current collector 1211 or on both surfaces of the negative electrode current collector 1211. As an example, such as... Figure 1 As shown, the negative electrode film layer 1212 is disposed on both sides of the negative electrode current collector 1211.

[0077] In some embodiments, the negative electrode film 1212 includes a negative electrode active material, which includes graphite.

[0078] For graphite, the interlayer spacing refers to the distance between carbon atom layers. For example, graphite is composed of sp... 2 Hybrid orbitals and three neighboring carbon atoms form three covalent bonds and arrange themselves into a planar hexagonal network structure. These network structures are formed by van der Waals forces to create parallel planes, thus constituting a layered structure. The distance between the layers is called the interlayer spacing, which can be represented by d002, and satisfies the condition d002 = nλ / 2Sinθ (n = 1, 2, 3, etc.), where n represents the diffraction order, λ represents the wavelength of the X-rays used, and θ represents the angle between the diffracted beam and the incident ray. The interlayer of graphite serves as both a lithium-ion storage space and a solid-phase diffusion channel for lithium ions.

[0079] In some embodiments, the interlayer spacing D of graphite satisfies: 0.33589 nm ≤ D ≤ 0.3364 nm. For example, the interlayer spacing D of graphite is 0.33589 nm, 0.33595 nm, 0.33598 nm, 0.336 nm, 0.3362 nm, 0.3364 nm, or any value within the above range. Setting the interlayer spacing of graphite within the above range, on the one hand, avoids increasing the resistance to lithium-ion insertion or extraction due to excessively small interlayer spacing. This not only helps reduce the expansion stress between graphite layers, giving it better structural stability and thus improving the cycle stability of the battery cell, but also helps improve the reversible capacity, thereby improving the capacity performance of the battery cell. At the same time, this interlayer spacing can reduce the diffusion barrier of lithium ions between graphite layers and reduce the phenomenon of lithium-ion retention by alleviating lithium insertion strain, thereby improving the rate performance and storage performance of lithium ions. On the other hand, it also avoids increasing the risk of graphite structure collapse during cycling due to excessively large interlayer spacing, thus improving the cycle life of the battery cell.

[0080] For graphite, the degree of graphitization refers to the degree of order in the graphite crystal structure of the material. The higher the degree of graphitization, the more ordered the carbon atoms in the material are, which can form a more ordered graphite crystal structure, thus reducing the number of surface defects.

[0081] In some embodiments, the graphitization degree g of graphite satisfies: 87.9% ≤ g ≤ 94.2%. For example, the graphitization degree g of graphite is 87.9%, 89%, 90%, 91%, 92%, 93%, 94%, 94.2%, or any value within the above range. When the graphitization degree of graphite material is not less than 70.9%, it is beneficial to improve the lithium intercalation capacity of graphite. Currently, the higher the graphitization degree, the higher the lithium intercalation capacity. For example, the graphitization degree of artificial graphite is generally around 94%, and the ratio of the average lattice parameter along the a-axis (La) to the average stacking height (Lc) is relatively large. It has relatively few active sites, exhibits excellent storage performance, and can reduce the formation of a thick solid electrolyte interface (SEI) film during the preparation of battery cells, reduce excessive consumption of active lithium ions, and reduce the impact on the storage life of battery cells. Therefore, setting the graphitization degree of graphite between 87.9% and 94.2% is beneficial to balancing the cycle storage performance and capacity performance of individual battery cells.

[0082] As an example, X-ray diffraction (XRD) was used, and the interlayer spacing of the (002) crystal plane of the first graphite was measured with reference to standard GB / T5618-2014. Specifically, as an example, after disassembling the battery cell, the negative electrode sheet was obtained. After washing the negative electrode sheet with water, it was filtered and dried to obtain graphite powder. The degree of graphitization was calculated using the Mering–Maire formula. The degree of graphitization g = [(3.440-d002) / (3.440-3.354)] × 100%, where d002 is the interlayer spacing of the (002) crystal plane of the first graphite.

[0083] In some embodiments, the specific capacity C of graphite satisfies: 330 mAh / g ≤ C ≤ 360 mAh / g. For example, the specific capacity C of artificial graphite is 330 mAh / g, 333 mAh / g, 335 mAh / g, 340 mAh / g, 350 mAh / g, 360 mAh / g, or any value within the above range. Meeting this specific capacity range not only reduces the impact on the storage performance of the battery cell due to excessively low specific capacity, but also helps to reduce the impact on the cycle performance of the battery cell due to excessively high specific capacity. Therefore, the specific capacity within the above range can balance the capacity performance, storage performance, and cycle performance of the battery cell, expanding the applicable scenarios for the battery cell.

[0084] It should be noted that the specific capacity value of graphite mentioned above is obtained by applying graphite to a single battery cell and testing the specific capacity of that cell. In other words, this specific capacity data reflects the performance of the single battery cell.

[0085] As an example, under test conditions of 25°C and 0.33C, the negative electrode sheets obtained from disassembling a single battery cell are cut to a specific size, and the negative electrode sheets and lithium sheets are assembled into a coin cell to test the specific capacity. For example, the delithiation specific capacity = delithiation capacity / mass of the negative electrode active material.

[0086] Therefore, the graphite in this embodiment of the application is beneficial to improving the cycle performance and storage performance of the battery cell while also taking into account its capacity performance.

[0087] For graphite, tap density refers to the density of the powder material after it has been compacted under certain conditions. It is a parameter used to measure the maximum density that a powder material can achieve after being vibrated in its natural packed state.

[0088] In some embodiments, the tap density T of graphite satisfies: 0.9 g / cm³ 3 ≤T≤1.3g / cm 3 For example, the tap density T of graphite is 0.9 g / cm³. 3 0.95g / cm 31.0g / cm 3 1.05g / cm 3 1.1g / cm 3 1.16 g / cm 3 1.2g / cm 3 1.3g / cm 3 Or any value within the above range. Setting the tap density of graphite within the above range will prevent the energy density of the battery cells from being too low, and will also prevent the expansion stress of the particles from concentrating during the lithium insertion / extraction process from being too high, which could easily lead to cracks and structural pulverization, thereby accelerating capacity decay.

[0089] As an example, the tap density of the negative electrode active material has a well-known meaning in the art and can be determined using instruments and methods known in the art. Specifically, as an example, after disassembling a battery cell, a negative electrode sheet is obtained. After washing the negative electrode sheet with water, it is filtered and dried to obtain graphite powder. The powder is then tapped, and the tap density is measured. For example, it can be determined using a powder tap density tester, referring to GB / T 5162-2006. The testing instrument can be a Dandong Baite BT-301. The test parameters are as follows: vibration frequency 250±15 times / minute, amplitude 3±0.2mm, number of vibrations 5000 times, and graduated cylinder 25mL. It should be noted that this test is based on batteries that have undergone formation or cycling, and the results are obtained after disassembly.

[0090] Optionally, the tap density T of graphite satisfies: 1.0 g / cm³ 3 ≤T≤1.25g / cm 3 For example, the tap density T of graphite is 1.0 g / cm³. 3 1.05g / cm 3 1.1g / cm 3 1.2g / cm 3 1.25g / cm 3 Or any value within the above range. This gives graphite a more suitable tap density, which helps to further improve the energy density and performance of individual battery cells.

[0091] Dv50 can refer to the particle size corresponding to 50% of the cumulative particle size distribution number of a sample, which means that 50% of the particles are smaller than Dv50.

[0092] In some embodiments, the Dv50 of graphite satisfies: 10.0 μm ≤ Dv50 ≤ 18.0 μm. For example, the Dv50 of graphite is 10.0 μm, 10.5 μm, 11.0 μm, 12.0 μm, 14.0 μm, 16.0 μm, 17.0 μm, 18.0 μm, or any value within the above range. This prevents the specific surface area of ​​graphite from being too large due to a Dv50, which would degrade the cycle storage performance of the battery cell, and also prevents the migration path of lithium ions within the graphite particles from being too large due to a Dv50, which would affect the rate performance. Therefore, setting the Dv50 of graphite within the above range is beneficial for balancing the cycle storage life and kinetic performance of the battery cell.

[0093] As an example, the volumetric particle size distribution can be determined using a particle size analyzer-laser diffraction method. Specifically, as an example, after disassembling a battery cell, the negative electrode sheet is obtained. After washing the negative electrode sheet with water, it is filtered and dried to obtain graphite powder. The powder can be measured using a laser diffraction scattering particle size analyzer according to the manufacturer's instructions, referring to standard GB / T19077-2016. For example, appropriate samples (e.g., positive electrode active material and negative electrode active material) are taken. The samples can be obtained directly from the powder (e.g., self-made or purchased) or from the powder obtained through disassembly of the battery product. The average volumetric particle size of the sample material is tested using a Malvern 2000 (MasterSizer 2000) laser particle size analyzer. Take an appropriate amount of the sample to be tested (the sample concentration should be 8-12% opacity), add 20ml of deionized water, and simultaneously incubate for 5 minutes (53KHz / 120W) to ensure complete dispersion of the sample. Then, determine the sample according to GB / T19077-2016 / ISO 13320:2009 standard.

[0094] Optionally, the Dv50 of graphite satisfies: 10.5μm ≤ Dv50 ≤ 16.6μm. For example, the Dv50 of graphite can be 10.5μm, 12μm, 13μm, 14μm, 15μm, 16.6μm, or any value within the above range. In this way, graphite with a more suitable Dv50 can further improve the cycle storage performance and kinetic performance of the battery cell.

[0095] In some embodiments, the one-sided density ρ of the negative electrode film layer 1212 satisfies: 100 mg / 1540.25 mm² 2 ≤ρ≤170mg / 1540.25mm 2 For example, the one-sided density ρ of the negative electrode film 1212 is 100 mg / 1540.25 mm. 2 110mg / 1540.25mm 2 120mg / 1540.25mm 2140mg / 1540.25mm 2 160mg / 1540.25mm 2 170mg / 1540.25mm 2 Or any value within the above range. This not only reduces the impact on the energy density of the battery cell due to insufficient coating weight, but also prevents the electrolyte from becoming difficult to wet due to excessive coating weight, which would prolong the diffusion path of lithium ions in the electrode and intensify polarization, thus affecting the service life of the battery cell.

[0096] As an example, the one-sided density of the negative electrode film has a well-known meaning in the art and can be measured using instruments and methods known in the art. Specifically, as an example, after disassembling the battery cell, the negative electrode sheet is obtained. Then, the thickness of the electrode sheet and the thickness of the current collector are measured respectively. The electrode sheet is then punched into a small circular piece with an area of ​​S1 (if it is a double-sided coated electrode sheet, the film layer on one side can be wiped off first), and its weight is weighed and recorded as M1. Then, the film layer of the weighed electrode sheet is wiped off, and the weight of the current collector is weighed and recorded as M0. The one-sided density = (M1-M0) / S1.

[0097] In some embodiments, graphite includes synthetic graphite. In specific applications, the appropriate type of graphite can be selected based on the actual needs of the battery cell.

[0098] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer substrate and a metal layer formed on at least one surface of the polymer substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0099] In some embodiments, the negative electrode film layer may optionally include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).

[0100] In some embodiments, the negative electrode film may optionally include a conductive agent. The conductive agent may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0101] In some embodiments, the negative electrode film may optionally include other additives, such as thickeners (e.g., sodium carboxymethyl cellulose (CMC-Na)).

[0102] In some embodiments, the negative electrode sheet can be prepared by dispersing the components used to prepare the negative electrode sheet, such as the negative electrode active material, conductive agent, binder and any other components, in a solvent (e.g., deionized water) to form a negative electrode slurry; coating the negative electrode slurry onto the negative electrode current collector, and then obtaining the negative electrode sheet after drying, cold pressing and other processes.

[0103] [Positive electrode plate]

[0104] The positive electrode sheet may include a positive current collector and a positive electrode film layer disposed on at least one surface of the positive current collector, the positive electrode film layer including a positive electrode active material.

[0105] As an example, the positive current collector has two surfaces opposite each other in its own thickness direction, and the positive electrode film layer is disposed on either or both of the two opposite surfaces of the positive current collector.

[0106] In some embodiments, the positive current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer substrate and a metal layer formed on at least one surface of the polymer substrate. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0107] In some embodiments, the positive electrode active material may be a known battery positive electrode active material. As an example, the positive electrode active material may include at least one of the following: lithium-containing transition metal oxides, lithium phosphates with an olivine structure, or materials with a spinel structure. However, this application is not limited to these materials, and other conventional materials that can be used as battery positive electrode active materials may also be used. These positive electrode active materials may be used alone or in combination of two or more. Examples of lithium transition metal oxides include, but are not limited to, lithium cobalt oxides (such as LiCoO2), lithium nickel oxides (such as LiNiO2), lithium manganese oxides (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxides, lithium manganese cobalt oxides, lithium nickel manganese oxides, and lithium nickel cobalt manganese oxides (such as LiNiO2). 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also known as NCM333), LiNi 0.5 Co0.2 Mn 0.3 O2 (also known as NCM523), LiNi 0.5 Co 0.25 Mn 0.25 O2 (also known as NCM211), LiNi 0.6 Co 0.2 Mn 0.2 O2 (also known as NCM622), LiNi 0.8 Co 0.1 Mn 0.1 O2 (also known as NCM811), lithium nickel cobalt aluminum oxide (such as LiNi) 0.85 Co 0.15 Al 0.05 At least one of O2 and its modified compounds. Examples of lithium phosphates with an olivine structure include, but are not limited to, lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), lithium iron phosphate and carbon composites, lithium manganese phosphate (such as LiMnPO4), lithium manganese phosphate and carbon composites, lithium manganese iron phosphate, and lithium manganese iron phosphate and carbon composites.

[0108] In some embodiments, the positive electrode film layer may optionally include a binder. As an example, the binder may include at least one selected from polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), PVDF-tetrafluoroethylene-propylene terpolymer, PVDF-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorinated acrylate resin.

[0109] In some embodiments, the positive electrode film may optionally include a conductive agent. As an example, the conductive agent may include at least one selected from superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0110] In some embodiments, the positive electrode sheet can be prepared by dispersing the above-mentioned components for preparing the positive electrode sheet, such as positive active material, conductive agent, binder and any other components, in a solvent (e.g., N-methylpyrrolidone) to form a positive electrode slurry, coating the positive electrode slurry onto the positive electrode current collector, and then obtaining the positive electrode sheet after drying, cold pressing and other processes.

[0111] [Electrolytes]

[0112] The electrolyte acts as a conductor of ions between the positive and negative electrodes. This application does not impose specific restrictions on the type of electrolyte; it can be selected according to requirements. For example, the electrolyte can be liquid, gel, or entirely solid.

[0113] In some embodiments, the electrolyte is an electrolyte solution. The electrolyte solution includes an electrolyte salt and a solvent.

[0114] In some embodiments, the electrolyte salt may be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalate borate, lithium dioxalate borate, lithium difluorodioxalate phosphate, and lithium tetrafluorooxalate phosphate.

[0115] In some embodiments, the solvent may be selected from at least one of ethylene carbonate, propylene carbonate, methyl ethyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butyl carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, sulfolane, dimethyl sulfone, methyl ethyl sulfone, and diethyl sulfone.

[0116] [Isolation membrane]

[0117] In some embodiments, the secondary battery also includes a separator. This application does not impose any particular limitation on the type of separator; any known porous separator with good chemical and mechanical stability can be selected.

[0118] In some embodiments, the material of the separator can be selected from at least one of glass fiber, nonwoven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator can be a single-layer film or a multi-layer composite film, without particular limitation. When the separator is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.

[0119] In some implementations, the positive electrode, negative electrode, and separator can be fabricated into an electrode assembly using a winding or stacking process.

[0120] In some embodiments, the battery cell may include an outer packaging. This outer packaging can be used to encapsulate the electrode assembly and electrolyte described above.

[0121] In some embodiments, the outer packaging of the battery cell can be a rigid shell, such as a hard plastic shell, an aluminum shell, or a steel shell. The outer packaging of the battery cell can also be a flexible package, such as a pouch. The material of the flexible package can be plastic; examples of plastics include polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0122] This application does not impose any particular limitation on the shape of the battery cell; it can be cylindrical, square, or any other arbitrary shape. For example, Figure 2 This is a schematic diagram of a battery cell according to one embodiment of this application.

[0123] Figure 3 This is a schematic diagram of the structure of a battery cell according to another embodiment of this application. Figure 3 As shown, the outer packaging of the battery cell 100 includes a housing 11 and a cover plate 13. The housing 11 may include a bottom plate and side plates connected to the bottom plate, the bottom plate and side plates forming a receiving cavity. The housing 11 has an opening communicating with the receiving cavity, and the cover plate 13 can be placed over the opening to close the receiving cavity. A positive electrode sheet, a negative electrode sheet, and a separator can be formed into an electrode assembly 12 through a winding process or a stacking process. The electrode assembly 12 is encapsulated within the receiving cavity. Electrolyte is immersed in the electrode assembly 12. The battery cell 100 may contain one or more electrode assemblies 12, which can be selected by those skilled in the art according to specific practical needs.

[0124] In some embodiments, the battery cells 100 can also be assembled into a battery module. The number of battery cells 100 contained in the battery module can be one or more, and the specific number can be selected by those skilled in the art according to the application and capacity of the battery module.

[0125] [Preparation methods for battery cells]

[0126] Figure 4 This is a flowchart illustrating the fabrication process of a battery cell according to an embodiment of this application. Figure 4 As shown, the method 200 for preparing a single battery cell includes the following steps:

[0127] S210, an oxidant solution is added to graphite raw material for pre-oxidation treatment to obtain a pre-oxidized graphite solution; wherein, the oxidant solution includes an oxidant;

[0128] S220, a reducing agent solution is added to a pre-oxidized graphite solution, and gas is generated in the redox reaction to obtain a graphite solution; wherein, the reducing agent solution includes a reducing agent;

[0129] S230 involves stirring, filtering, washing, and drying a graphite solution to obtain graphite.

[0130] S240 utilizes graphite to prepare negative electrode sheets in order to obtain battery cells.

[0131] Specifically, in S210, the oxidant pre-oxidizes the graphite raw material, which micro-expands the edge layers of the graphite raw material, making it easier for the reducing agent to intercalate into the interlayer of the graphite. Simultaneously, the oxidant oxidizes the surface of the graphite raw material, removing some defect sites. This helps reduce irreversible lithium loss during the first charge-discharge cycle of the battery cell, thereby improving the storage performance of the battery cell.

[0132] In S220, through the intercalation of the reducing agent and the redox reaction with the oxidizing agent, gas can be generated between the layers of the graphite raw material. As the gas escapes from the interlayer, it can generate stress in the direction of the graphite interlayer spacing and reduce the van der Waals forces between the layers, thereby increasing the interlayer spacing of the graphite to achieve the layer expansion process.

[0133] It should be noted that the aforementioned reducing agent can also be called an intercalating agent, and this application does not limit this terminology. The intercalating agent refers to an agent capable of entering the interlayer space of graphite and interacting with the aforementioned oxidizing agent, the resulting gas of which can alter the interlayer spacing of the graphite.

[0134] In step S230, by-products, unreacted raw materials, and impurities from the reaction are removed through stirring, filtration, washing, and drying, thereby obtaining an oxidation precursor with high purity and quality. For example, in some embodiments, the pH of the graphite solution is maintained between 6 and 7 through washing, which reduces the residue of acid molecules such as oxidants and reductants on the graphite surface, improving the purity and stability of the product.

[0135] In S240, the graphite prepared by the above method not only reduces the complexity of the process due to high-temperature heat treatment, but also allows for layer expansion of the graphite. Simultaneously, the increased interlayer spacing of the graphite reduces the volume expansion of graphite particles during cycling, thereby minimizing the loss of excessive active lithium due to the rupture and repair of the SEI film caused by the expansion and contraction of graphite particles during cycling. Therefore, the above approach can also improve the cycle performance of individual battery cells.

[0136] Furthermore, the graphite prepared by the above method, when using graphite with the same specific capacity, can increase its interlayer spacing. The gas generation causes the graphite lattice fringes to bend, preventing the graphite lattice growth fringes from breaking or the graphite sheets from peeling off. Therefore, the number of lithium storage sites between graphite layers is not reduced, maintaining its specific capacity and benefiting the capacity performance of the battery cell.

[0137] Therefore, the graphite prepared in this application can increase its interlayer spacing under the same specific capacity condition, which is beneficial to improving the cycle performance and storage performance of the battery cell while taking into account the capacity performance.

[0138] In some embodiments, the interlayer spacing D of graphite satisfies: 0.33589 nm ≤ D ≤ 0.3364 nm. For example, the interlayer spacing D of graphite is 0.33589 nm, 0.33595 nm, 0.33598 nm, 0.336 nm, 0.3362 nm, 0.3364 nm, or any value within the above range; the specific capacity C of graphite satisfies: 330 mAh / g ≤ C ≤ 360 mAh / g. For example, the specific capacity C of artificial graphite is 330 mAh / g, 333 mAh / g, 335 mAh / g, 340 mAh / g, 350 mAh / g, 360 mAh / g, or any value within the above range.

[0139] In some embodiments, the degree of graphitization g of graphite satisfies: 87.9% ≤ g ≤ 94.2%. For example, the degree of graphitization g of graphite is 87.9%, 89%, 90%, 91%, 92%, 93%, 94%, 94.2% or any value within the above range.

[0140] In some embodiments, the oxidant includes at least one of nitric acid, sulfuric acid, ammonium persulfate, potassium permanganate, potassium dichromate, hydrogen peroxide, and ozone. All of the above oxidants have strong oxidizing properties and can selectively oxidize and etch the edge active sites of graphite (i.e., lithium-consuming active sites), introducing oxygen-containing functional groups (e.g., hydroxyl, carboxyl, epoxy, etc.) at the edges or between layers of graphite.

[0141] In some embodiments, the reducing agent comprises an organic acid, which includes at least one of a carboxylic acid group and a sulfonic acid group. Using the aforementioned weakly acidic organic acid can neutralize the strong oxidizing power of the oxidizing agent and induce a redox reaction with the aforementioned oxygen-containing functional groups. This redox reaction transforms the aforementioned marginal active sites into more stable SP sites. 2 The conjugated structure effectively reduces the active sites on the graphite surface, thereby decreasing the irreversible lithium consumption during SEI film formation. This not only increases the interlayer spacing of graphite but also improves the cycle performance of individual battery cells.

[0142] In some embodiments, the reducing agent includes at least one selected from formic acid, acetic acid, propionic acid, oxalic acid, citric acid, benzoic acid, p-toluenesulfonic acid, and benzenesulfonic acid. Using the aforementioned reducing agents with strong reducing properties, the reducing agent can be inserted into the interlayer space of graphite through van der Waals forces or hydrogen bonding, thereby further expanding the interlayer spacing. Simultaneously, the reducing agent may form hydrogen bonds with functional groups (such as hydroxyl groups) on the graphite surface through its carboxyl groups, thereby stabilizing and expanding the interlayer spacing.

[0143] In some embodiments, based on the total mass of the graphite solution, the mass content A of the reducing agent satisfies: 16% ≤ A ≤ 50.4%. For example, the mass content A of the reducing agent is 16%, 16.5%, 20%, 30%, 50%, 50.4%, or any value within the above range. This ensures that the redox reaction is not incomplete due to too low a mass content of the reducing agent, thus reducing the layer expansion effect, and that excessive reduction due to too high a mass content of the reducing agent does not damage the interlayer structure.

[0144] Optionally, based on the total mass of the graphite solution, the mass content A of the reducing agent satisfies: 16% ≤ A ≤ 20%. For example, the mass content A of the reducing agent is 16%, 17%, 18%, 20%, or any value within the above range. This is beneficial for further improving the performance of the battery cell.

[0145] In some embodiments, based on the total mass of the graphite solution, the mass content B of the oxidant satisfies: 20% ≤ B ≤ 75%. For example, the mass content B of the oxidant is 20%, 25%, 30%, 40%, 50%, 60%, 75%, or any value within the above range. Setting the mass content of the oxidant within the above range is beneficial in reducing insufficient pre-oxidation reaction due to an excessively low oxidant mass ratio, thus reducing the delamination effect. It is also beneficial in reducing over-oxidation of graphite due to an excessively high oxidant mass content, which could lead to partial peeling of graphite flakes, forming a looser layered structure and reducing cycle performance.

[0146] Optionally, based on the total mass of the graphite solution, the mass content B of the oxidant satisfies: 55% ≤ B ≤ 68%. For example, the mass content B of the oxidant is 55%, 58%, 60%, 61%, 64%, 68%, or any value within the above range. This is beneficial for further improving the performance of the battery cell.

[0147] In some embodiments, the pre-oxidation treatment temperature E satisfies the condition: 20℃ ≤ E ≤ 60℃. For example, the pre-oxidation treatment temperature E is 20℃, 25℃, 30℃, 40℃, 50℃, 60℃, or any value within the above range. For the pre-oxidation treatment, the treatment temperature can control the degree of pre-oxidation, thereby affecting the interlayer spacing of graphite. Simultaneously, the higher the treatment temperature, the larger the interlayer spacing of graphite. Setting the pre-oxidation treatment temperature within the above range can achieve the elimination of surface active sites and the expansion of graphite interlayer spacing. It also helps to reduce graphite particle breakage due to excessive oxidation and layer expansion, thereby exposing more active sites. Therefore, this pre-oxidation treatment temperature is beneficial to improving the performance of the battery cell.

[0148] In some embodiments, the concentration w of the oxidant solution satisfies the following condition: 50% ≤ w ≤ 90%. For example, the concentration w of the oxidant solution is 50%, 55%, 57%, 60%, 70%, 80%, 85%, 90%, or any value within the above range. This ensures that the reaction is not incomplete due to an excessively low concentration of the oxidant solution, which could reduce the layer-widening effect, and that excessively high concentrations of the oxidant solution can cause over-oxidation and damage the graphite structure.

[0149] In some embodiments, the molecular weight of the oxidant is greater than that of the reductant. Specifically, by selecting an oxidant with a larger molecular weight, the interlayer spaces of graphite can be effectively expanded, which is beneficial for the intercalation process of the reductant. Subsequently, smaller reductant molecules can more easily penetrate into the expanded interlayer spaces of graphite, thereby effectively increasing the interlayer spacing, which is beneficial for the insertion and extraction of lithium ions, thereby improving the performance of the battery cell.

[0150] In some embodiments, the graphite raw material includes at least one of artificial graphite, modified natural graphite, mesophase carbon microspheres, petroleum coke, and needle coke. The graphite raw material in this application is compatible with multiple carbon sources, and suitable graphite raw materials can be selected according to actual needs to control the microcrystalline orientation and particle morphology of graphite, thereby enhancing the lithium-ion transport path and electrode processing performance.

[0151] In some embodiments, the pre-oxidation treatment time is between 10 min and 24 h. For example, the pre-oxidation treatment time is 10 min, 20 min, 30 min, 1 h, 2 h, 4 h, 8 h, 15 h, 20 h, 24 h, or any value within the above range. This ensures that the pre-oxidation treatment time is not too short, resulting in insufficient layer expansion, nor too long, causing the graphite structure to collapse.

[0152] In some embodiments, the stirring speed is between 100 rpm and 800 rpm. For example, the stirring speed is 100 rpm, 150 rpm, 200 rpm, 300 rpm, 400 rpm, 500 rpm, 600 rpm, 700 rpm, 800 rpm, or any value within the above range. Controlling the stirring speed during the preparation process within the above range helps to reduce uneven reaction due to excessively slow stirring speed, and also helps to reduce damage to the graphite structure due to excessively fast stirring speed.

[0153] Therefore, the time and stirring speed of the above-mentioned pre-oxidation treatment are beneficial to further improve the layer expansion effect, thereby improving the performance of the battery cell.

[0154] This application also provides a battery device and an electrical device. The battery device and electrical device of this application will now be described with appropriate reference to the accompanying drawings.

[0155] [Battery Device]

[0156] This application provides a battery device including one or more battery cells as described in the above embodiments. When there are multiple battery cells, they are connected in series, parallel, or mixed connections via a busbar.

[0157] In some embodiments, the battery device may be a battery pack, which includes a housing and individual battery cells, with the individual battery cells or battery modules housed within the housing.

[0158] In some embodiments, the battery device may be located within an energy storage device. Energy storage devices include energy storage containers, energy storage cabinets, etc.

[0159] Figure 5 This is a schematic diagram of a battery device according to one embodiment of this application. Figure 6 This is a schematic diagram of the battery device according to one embodiment of this application. (Refer to...) Figure 5 and Figure 6 The battery device 400 may include a battery box and a plurality of battery cells 100 disposed within the battery box. The battery box includes an upper box 401 and a lower box 402, the upper box 401 covering the lower box 402 to form a closed space for accommodating the battery cells 100. The plurality of battery cells 100 may be arranged in any manner within the battery box.

[0160] [Electrical appliances]

[0161] This application also provides an electrical device that includes the battery device described in the foregoing embodiments. The electrical device includes at least one of the battery cell 100 or battery device 400 provided in this application. The battery cell 100 or battery device 400 can be used as a power source for the electrical device or as an energy storage unit for the electrical device. The electrical device may include, but is not limited to, mobile devices (e.g., mobile phones, laptops, etc.), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc.

[0162] For example, Figure 7 This is a schematic diagram of the structure of an electrical device according to one embodiment of this application. Figure 7As shown, the electrical device is vehicle 1, which can be a gasoline-powered vehicle, a natural gas-powered vehicle, or a new energy vehicle. New energy vehicles can be pure electric vehicles, hybrid electric vehicles, or range-extended electric vehicles, etc. A motor 500, a controller 600, and a battery device 400 can be installed inside vehicle 1. The controller 600 controls the battery device 400 to supply power to the motor 500. For example, the battery device 400 can be installed at the bottom, front, or rear of vehicle 1. The battery device 400 can be used to power vehicle 1; for example, it can serve as the operating power source for vehicle 1's electrical system, such as meeting the power requirements for starting, navigation, and operation. In another embodiment of this application, the battery device 400 can not only serve as the operating power source for vehicle 1 but also as the driving power source, replacing or partially replacing gasoline or natural gas to provide driving power to vehicle 1.

[0163] As the electrical device, either the battery cell 100 or the battery device 400 can be selected according to its usage requirements.

[0164] The electrical device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. To meet the high power and high energy density requirements of the battery for this electrical device, a single battery cell of 100 or a battery pack of 400 can be used.

[0165] Another example of an electrical device could be a mobile phone, tablet, or laptop. These devices typically require a slim and lightweight design and can use a single battery cell (100) as their power source.

[0166] The following describes embodiments of this application. The embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the embodiments, they are performed according to the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments used, unless otherwise specified, are all conventional products that can be obtained commercially.

[0167] [Examples and Comparative Examples]

[0168] [Example 1]

[0169] (1) Preparation of negative electrode sheet:

[0170] Preparation of graphite: Take 2.5 g of artificial graphite raw material with a specific capacity of 360 mAh / g. Place it in a 250 ml beaker, add 5 ml of concentrated nitric acid (molecular weight 63.012 g / mol), and slightly tilt the beaker to ensure the concentrated nitric acid fully contacts and wets the graphite. Then, let the beaker stand at 20°C for 1 hour to allow the concentrated nitric acid to pre-oxidize the graphite, obtaining a pre-oxidized graphite solution. Subsequently, add a magnetic stir bar to the pre-oxidized graphite solution and place the beaker on a magnetic stirrer. Then, slowly add 4 ml of formic acid (molecular weight 46.0254 g / mol) to the beaker, and obtain a graphite solution through a redox reaction. Stir the graphite solution thoroughly for 3 hours. Then, filter and wash the stirred graphite solution with water using a vacuum filtration device, repeatedly washing with deionized water until the pH value of the solution is between 6 and 7. The filtered product was then thoroughly dried in a forced-air drying oven to obtain artificial graphite. The artificial graphite exhibited an interlayer spacing of 0.33589 nm, a reducing agent content of 33.7% of the solution, a degree of graphitization of 94.2%, and a tap density of 1.06 g / cm³. 3 The Dv50 of artificial graphite is 15.5um.

[0171] Preparation of the negative electrode sheet: Artificial graphite, sodium carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), and conductive agent (SP) were mixed in a mass ratio of 94.5:1.5:2.5:1.5 to obtain a uniform slurry. A water-based negative electrode slurry was used to coat both sides of a copper foil. After drying, cold pressing, and cutting, the negative electrode sheet was obtained. The single-sided density of the negative electrode film was 100 mg / 1540.25 mm². 2 .

[0172] (2) Preparation of the positive electrode sheet:

[0173] An oil-based positive electrode slurry was prepared using lithium iron phosphate (LiFePO4), SP, and polyvinylidene fluoride (PVDF) in a mass ratio of 90:5:5. After being mixed evenly, the slurry was coated on both sides of an aluminum foil, dried, cold-pressed, and cut to obtain the positive electrode sheet.

[0174] (3) Separating membrane:

[0175] The separator includes a base film, which is a polyethylene (PE) film with a thickness of 7 μm. An inorganic coating with a thickness of 2 μm is disposed on the side of the base film facing the negative electrode. The inorganic coating includes alumina ceramic particles.

[0176] (4) Preparation of electrolyte:

[0177] In an argon atmosphere glove box (H2O < 0.1 ppm, O2 < 0.1 ppm), ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) were mixed in a volume ratio of 1:1:1 to obtain an organic solvent. LiPF6 was then dissolved in the organic solvent to prepare an electrolyte with a concentration of 1 mol / L.

[0178] (5) Preparation of battery cells:

[0179] Preparation of a single battery cell: The positive electrode, separator, and negative electrode are stacked in sequence, with the separator positioned between the positive and negative electrodes to isolate them. The electrode assembly is then wound to obtain an electrode assembly. The tabs of the electrode assembly are connected to the end cap (e.g., by welding the tabs to the end cap using a connecting member). The electrode assembly is placed in an aluminum casing, dried, and then injected with electrolyte. Finally, it is encapsulated to obtain a single battery cell.

[0180] [Examples 2-3]

[0181] The difference between Examples 2-3 and Example 1 is that the pre-oxidation temperature is different, resulting in different interlayer spacing and graphitization degree of artificial graphite.

[0182] [Examples 4-5]

[0183] The difference between Examples 4-5 and Example 2 is that the mass content of the reducing agent is different, resulting in different interlayer spacing and graphitization degree of the artificial graphite.

[0184] [Examples 6-7]

[0185] The difference between Examples 6-7 and Example 2 is that the gram capacity is different.

[0186] [Comparative Example 1]

[0187] The difference between Comparative Example 1 and Example 1 is that the artificial graphite was not subjected to layer expansion treatment.

[0188] [Comparative Example 2]

[0189] The difference between Comparative Example 2 and Example 6 is that their gram capacity is different.

[0190] [Comparative Example 3]

[0191] The difference between Comparative Example 3 and Example 7 is that their gram capacity is different.

[0192] Table 1 shows the specific parameters of the negative electrode active material during the preparation of the battery cell.

[0193] Table 1. Parameter results for Examples 1-7 and Comparative Examples 1-3

[0194]

[0195] In Table 1, "mass content of reducing agent" refers to the mass content of reducing agent based on the total mass of the graphite solution.

[0196] The battery cells obtained in Examples 1-7 and Comparative Examples 1-3 were subjected to performance tests. The test results are shown in Table 2 below.

[0197] Table 2 Performance test results of Examples 1-7 and Comparative Examples 1-3

[0198]

[0199] This application characterizes the battery's cycle performance by measuring capacity retention after 240 cycles. A higher capacity retention rate after 240 cycles indicates better capacity retention after 240 cycles, meaning better cycle performance. For battery cells with graphite as the negative electrode active material, cycle degradation becomes more pronounced with increasing cycle count, a well-known fact in the art. Therefore, those skilled in the art will understand that, based on the difference in capacity retention rate after 240 cycles between the embodiments and comparative examples, the cycle performance of the embodiments in this application is superior to that of the comparative examples when the number of cycles increases.

[0200] Figure 8 This is a TEM image of the graphite in Embodiment 3 of this application. Figure 8 As shown, transmission electron microscopy (TEM) tests revealed that the graphite in Example 3 had a large interlayer spacing, and the lattice fringes of the graphite exhibited a curved shape.

[0201] Figure 9 The images show the XRD patterns of graphite from Examples 2-3 and Comparative Example 1 of this application. Referring to Table 1, it can be seen that the graphite in Example 5 has a larger interlayer spacing and a lower degree of graphitization, while the graphite in Comparative Example 1 has a smaller interlayer spacing and a higher degree of graphitization. Figure 9 As shown, within a certain range, as the interlayer spacing increases, the degree of graphitization gradually decreases, causing the characteristic diffraction peaks to shift to a lower angle, i.e., to the left, and the diffraction angle also decreases accordingly.

[0202] Figure 10 The Raman spectra of graphite from Examples 2-3 and Comparative Example 1 of this application are shown. Figure 10 As shown, ID is the intensity of the D peak in the Raman spectrum of graphite, and IG is the intensity of the G peak in the Raman spectrum of graphite. The higher the ratio of ID / IG, the higher the degree of defects and disorder in the material, resulting in lower storage performance of the battery cell.

[0203] As shown in Table 2, and based on Examples 1-5 and Comparative Example 1, Examples 6 and Comparative Example 2, and Examples 7 and Comparative Example 3, it can be seen that in the technical solution of this application, the above-mentioned graphite is used in the examples, which can improve the interlayer spacing of graphite, which is beneficial to improving the cycle performance and storage performance of battery cells while also taking into account their capacity performance.

[0204] As shown in Table 2, and based on Examples 2-3 and Example 1, within a certain range, increasing the pre-oxidation temperature can increase the interlayer spacing of graphite and decrease its graphitization degree. This is because as the temperature increases, the redox reaction becomes more intense, and the oxidant etches the graphite end faces more deeply, thus increasing the interlayer spacing. However, this process also generates more oxygen-containing functional groups, thereby increasing the consumption of active lithium and reducing the performance of the battery cell. Therefore, further controlling the pre-oxidation temperature is beneficial for expanding the graphite interlayer spacing while improving the cycle performance and storage performance of the battery cell, while also considering its capacity performance.

[0205] As shown in Table 2, and based on Examples 4-5 and Example 2, within a certain range, reducing the mass content of the reducing agent is beneficial for increasing the mass content of the oxidant, resulting in a better initial layer expansion effect. This, in turn, allows more reducing agent to enter the interlayer space, enabling a continuous layer expansion process. Therefore, reducing the mass content of the reducing agent can increase the interlayer spacing of graphite and reduce its graphitization degree, which is beneficial for improving the cycle performance and storage performance of battery cells while also maintaining their capacity performance.

[0206] As shown in Table 2, based on Examples 6-7 and Example 2, within a certain range, reducing the specific capacity of graphite can increase the interlayer spacing and decrease its graphitization degree. With the decrease in specific capacity, more active sites are exposed on the graphite end faces, resulting in less graphite volume expansion and rebound, which is beneficial for improving the cycle performance of the battery cell. However, more active sites may increase side reactions in the electrolyte, thereby consuming more active lithium and reducing the storage performance of the battery cell.

[0207] It should be noted that this application is not limited to the above-described embodiments. The above embodiments are merely examples, and any embodiments with the same structure and effect as the technical concept within the scope of this application are included in the technical scope of this application. Furthermore, various modifications that can be conceived by those skilled in the art to the embodiments, and other ways of constructing by combining some of the constituent elements of the embodiments, without departing from the spirit of this application, are also included in the scope of this application.

[0208] The following is a brief description of the testing methods for the physicochemical and performance parameters involved in the embodiments of this application. It should be understood that the following testing methods are only examples, and other testing methods known in the art can also be used for testing.

[0209] 1. Capacity retention test

[0210] The lithium-ion battery was placed at 25℃ and left to stand for 30 minutes. It was then discharged at a constant current rate of 0.5C to 2.0V, left to stand for 10 minutes, and charged at a constant current rate of 0.33C to 3.8V. It was then charged at a constant voltage of 3.8V until the current rate dropped to 0.05C. After that, it was left to stand for 10 minutes, and then discharged at a constant current rate of 1C to 2.0V, followed by a discharge at 0.33C to 2.0V. This result is recorded as Cap1. The battery cells were then subjected to a cycle charge-discharge test in the above manner. The discharge capacity after the 240th cycle was recorded as Cap240. The capacity retention rate of the battery cell after 240 cycles is calculated as C = [Cap240 / Cap1] × 100%. A larger C value indicates less capacity loss and better cycle performance.

[0211] Similarly, lithium-ion batteries were stored at 60°C, 3.8V, and 0.33C for 90 days, and the capacity retention of individual battery cells was measured.

[0212] 2. Morphology testing of negative electrode active materials

[0213] The morphology of the negative electrode active material can be characterized by transmission electron microscopy (model Thermo Scientific-TalosF200S G2).

[0214] As an example, at 25°C, a single battery cell was charged to 3.8V at a constant current of 0.33C and discharged to 2.0V at a constant current of 0.33C to obtain a battery cell with 0% SOC. The negative electrode was then removed from the battery cell, washed with water, filtered, and dried to obtain graphite powder, thus obtaining artificial graphite powder. The morphology of the artificial graphite was characterized using transmission electron microscopy and in accordance with standard GB / T23413-2009.

[0215] 3. Raman spectroscopy testing

[0216] Measurements were performed using a Raman spectrometer. Specifically, a laser confocal microscopy Raman spectrometer (e.g., a high-precision Renishaw laser confocal microscopy Raman spectrometer) was used.

[0217] As an example, at 25°C, a single battery cell was charged to 3.8V at a constant current of 0.33C and discharged to 2.0V at a constant current of 0.33C to obtain a battery cell with 0% SOC. The negative electrode was then removed from the battery cell, washed with water, filtered, and dried to obtain graphite powder, thus obtaining artificial graphite powder. The Raman spectrum of the graphite was then tested using a Raman spectrometer, referring to GB / T33252-2016.

Claims

1. A battery cell, characterized in that, include: A negative electrode sheet, the negative electrode sheet comprising a negative current collector and a negative electrode film layer disposed on at least one side surface of the negative current collector, the negative electrode film layer comprising a negative electrode active material, the negative electrode active material comprising graphite; The interlayer spacing D of the graphite satisfies: 0.33589nm ≤ D ≤ 0.3364nm; The specific capacity C of the graphite satisfies: 330mAh / g≤C≤360mAh / g.

2. The battery cell according to claim 1, characterized in that, The degree of graphitization g of the graphite satisfies: 87.9% ≤ g ≤ 94.2%.

3. The battery cell according to claim 1 or 2, characterized in that, The tap density T of the graphite satisfies: 0.9 g / cm³ 3 ≤T≤1.3g / cm 3 Optionally, the tap density T of the graphite satisfies: 1.0 g / cm³. 3 ≤T≤1.25g / cm 3 .

4. The battery cell according to any one of claims 1 to 3, characterized in that, The graphite has a Dv50 that satisfies: 10.0 μm ≤ Dv50 ≤ 18.0 μm; optionally, the graphite has a Dv50 that satisfies: 10.5 μm ≤ Dv50 ≤ 16.6 μm.

5. The battery cell according to any one of claims 1 to 4, characterized in that, The single-sided density ρ of the negative electrode film layer satisfies: 100mg / 1540.25mm² 2 ≤ρ≤170mg / 1540.25mm 2 .

6. The battery cell according to any one of claims 1 to 5, characterized in that, The graphite includes synthetic graphite.

7. A method for preparing a single battery cell, characterized in that, include: An oxidant solution is added to graphite raw material for pre-oxidation treatment to obtain a pre-oxidized graphite solution; wherein, the oxidant solution includes an oxidant; A reducing agent solution is added to the pre-oxidized graphite solution, and gas is generated in the redox reaction to obtain a graphite solution; wherein, the reducing agent solution includes a reducing agent; The graphite solution is stirred, filtered, washed, and dried to obtain graphite; The negative electrode sheet is prepared using the graphite to obtain the battery cell.

8. The preparation method according to claim 7, characterized in that, The oxidant includes at least one of nitric acid, sulfuric acid, ammonium persulfate, potassium permanganate, potassium dichromate, hydrogen peroxide, and ozone.

9. The preparation method according to claim 7 or 8, characterized in that, The reducing agent includes an organic acid, which includes at least one of a carboxylic acid group and a sulfonic acid group.

10. The preparation method according to claim 9, characterized in that, The reducing agent includes at least one of formic acid, acetic acid, propionic acid, oxalic acid, citric acid, benzoic acid, p-toluenesulfonic acid, and benzenesulfonic acid.

11. The preparation method according to any one of claims 7 to 10, characterized in that, Based on the total mass of the graphite solution, the mass content A of the reducing agent satisfies: 16% ≤ A ≤ 50.4%; optionally, the mass content A of the reducing agent satisfies: 16% ≤ A ≤ 20%.

12. The preparation method according to any one of claims 7 to 11, characterized in that, Based on the total mass of the graphite solution, the mass content B of the oxidant satisfies: 20% ≤ B ≤ 75%; optionally, the mass content B of the oxidant satisfies: 55% ≤ B ≤ 68%.

13. The preparation method according to any one of claims 7 to 12, characterized in that, The temperature E of the pre-oxidation treatment satisfies: 20℃≤E≤60℃.

14. The preparation method according to any one of claims 7 to 13, characterized in that, The concentration w of the oxidant solution satisfies: 50% ≤ w ≤ 90%.

15. The preparation method according to any one of claims 7 to 14, characterized in that, The molecular weight of the oxidant is greater than that of the reducing agent.

16. The preparation method according to any one of claims 7 to 15, characterized in that, The graphite raw material includes at least one of artificial graphite, modified natural graphite, mesophase carbon microspheres, petroleum coke, and needle coke.

17. The preparation method according to any one of claims 7 to 16, characterized in that, The pre-oxidation treatment time F satisfies: 10min≤F≤24h, and the stirring speed V satisfies: 100rpm≤V≤800rpm.

18. A battery device, characterized in that, include: The battery cell according to any one of claims 1-6, and / or the battery cell obtained by the preparation method according to any one of claims 7-17.

19. An electrical appliance, characterized in that, Includes the battery device as described in claim 18.